2010
DOI: 10.2174/1874401x01003010154
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Preferences of Spotted Seatrout, Cynoscion nebulosus, in Coastal Louisiana: A Step Towards Informing Spatial Management in Estuarine Ecosystems~!2009-10-29~!2010-04-05~!2010-06-29~!

Abstract: Louisiana wetlands are disappearing at a dramatic rate, providing an impetus for identifying the relative value to fishes of a matrix of estuarine habitat types. The distribution, relative abundance, biomass, and length of spotted seatrout, Cynoscion nebulosus (Cuvier) were examined in Barataria Bay, Louisiana, in relation to habitat type and abiotic variables. Spotted seatrout were collected from three sites located along a salinity gradient. Each site contained the three habitat types of interest: marsh edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Specifically, spotted seatrout were affected by temperature and salinity, and presence was determined more by these two factors than by the habitat. This result is consistent with the findings of MacRae and Cowan [33] and to a study of acoustically tagged spotted seatrout by Callihan [34], found strong responses of spotted seatrout to low salin-ity events, and seasonal preferences for reef (both natural and artificial) habitats. Callihan [34] observed that spotted seatrout were frequently located near reef habitats in the spring and summer months, though this research is still ongoing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, spotted seatrout were affected by temperature and salinity, and presence was determined more by these two factors than by the habitat. This result is consistent with the findings of MacRae and Cowan [33] and to a study of acoustically tagged spotted seatrout by Callihan [34], found strong responses of spotted seatrout to low salin-ity events, and seasonal preferences for reef (both natural and artificial) habitats. Callihan [34] observed that spotted seatrout were frequently located near reef habitats in the spring and summer months, though this research is still ongoing.…”
Section: Discussionsupporting
confidence: 92%
“…Nearly twice as many spotted seatrout were collected over the artificial reef, and these fish were roughly 20% larger than those collected over the mud bottom, indicating the artificial reef supports a higher biomass of spotted seatrout. While spotted seatrout were larger at the reef, abundance as not difference between habitats, which is similar to results found be MacRae and Cowan [33], and indicates that seasonal influences have a more pronounced effect on the distribution of spotted seatrout than the presence of reef structure. Specifically, spotted seatrout were affected by temperature and salinity, and presence was determined more by these two factors than by the habitat.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that some important variables in the habitat usage of these species may not have been included. For example, biotic components: spawning location, prey and predator density, movement patterns of individuals were not considered in this study (MacRae and Cowan, 2010). However, we were able to examine several variables simultaneously that were related to environment suitability providing timely information for conservation and management of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Subadult RDM (age 1-3) associate with shallow seagrass beds and habitat edges (but see Mahoney et al, 2018), as well as oyster reefs, saltmarshes, and sand flats (Bacheler et al, 2009;Dance and Rooker, 2015;Fodrie et al, 2015;Moulton et al, 2017). Subadult and early adult SPT (age 0-2, of similar size to age 1-3 RDM) associate with seagrass beds to some degree, but they appear to mainly utilize unvegetated substrate and loose shell bottom (MacRae and Cowan, 2010;Moulton et al, 2017).…”
Section: Experimental Designmentioning
confidence: 99%